Passée la porte, il n’y a rien que du vent : Southern et Western, du désenchantement au crépuscule - Christian Viviani (Revue LISA)
Southern melodrama can be understood as a generic enclave rooted in traditional melodrama which borrows from the Western genre not only its interrelated historical framework, particular rites, but its recognizable characters, decors, costumes and coded situations. The geographic situation of the South with its complex history enable more or less perceptible shifts from the Southern to the Western. Dooming to failure the hegemonic self-delusion of the white Southern master and the revengeful white trash characters, disenchanted “twilight Westerns” announce the ideological challenge that marked the Westerns of the 1960s and 1970s. The premonitory intuition of these films constitutes the red thread of the present article.